Case report: Invasive fungal infection in a patient with a rare CVID-causing gene (TNFRSF13B) mutation undergoing AML treatment - Tabak, Carine; Hyter, Stephen; Yacoub, Abdulraheem; Byrd, Kenneth; McGuirk, Joseph; Godwin, Andrew K.; Abdelhakim, Haitham (Frontiers in Oncology, 2023)
Acute myeloid leukemia (AML) is a complex diagnosis that puts patients at a higher risk for developing infections, particularly invasive fungal infections (IFI). Mutations in TNFRSF13B have been shown to cause dysfunction in B-cell homeostasis and differentiation, making it a risk factor for developing immunodeficiency syndromes. In this case, a male patient in his 40s presented to our emergency department (ED) with symptoms leading to a diagnosis of AML with concurrent mucormycosis of the lungs and sinuses. Targeted next generation sequencing (NGS) of the patient’s bone marrow showed, among other variants, a loss of function mutation in the TNFRSF13B gene. While most patients present with fungal infections after prolonged periods of neutropenia associated with AML treatment, this case presented with IFI at diagnosis without neutropenia suggesting an immunodeficiency syndrome. The concurrent IFI and AML diagnoses create a delicate balance between treatment of the infection and the malignancy. This case highlights the risk of infection in patients receiving chemotherapy, especially those with unrecognized immunodeficiency syndromes, and emphasizes the importance of NGS for prognosis and treatment.